PENTINGNYA PERENCANAAN SDM PERUSAHAAN DALAM ERA DIGITALISASI - Ghazi Umar; Sri Yanthy Yosepha (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to discuss and analyze a rapid development of digitalization which in turnbrings rapid changes in HR planning and strategy in the future. What are the various formsof HR planning and strategies that need to be carried out in order to provide maximumresults for both employees and the company's organization. The research method used is aqualitative research method, and the qualitative method used is a type of library research.Literature study is a type of channel type qualitative research method. The pattern of needs inorder to adapt to conditions amid the dynamic changes in the global business environmentand in the growth of various digital innovations has a direction towards the fact thatcompanies are forced to adapt to various changes such as the way of working andredesigning their business forms.